Tracking antigen‐specific CD4+ T cells throughout the course of chronic Leishmania major infection in resistant mice. Issue 2 (11th December 2012) - Pagán, Antonio J.; Peters, Nathan C.; Debrabant, Alain; Ribeiro‐Gomes, Flavia; Pepper, Marion; Karp, Christopher L.; Jenkins, Marc K.; Sacks, David L.
<x xml:space="preserve">Abstract</x> Primary Leishmania major infection typically produces cutaneous lesions that not only heal but also harbor persistent parasites. While the opposing roles of CD4+ T‐cell‐derived IFN‐γ and IL‐10 in promoting parasite killing and persistence have been well established, how these responses develop from naïve precursors has not been directly monitored throughout the course of infection. We used peptide:Major Histocompatibility Complex class II (pMHCII) tetramers to investigate the endogenous, parasite‐specific primary CD4+ T‐cell response to L. major in mice resistant to infection. Maximal frequencies of IFN‐γ+ CD4+ T cells were observed in the spleen and infected ears within a month after infection and were maintained into the chronic phase. In contrast, peak frequencies of IL‐10+ CD4+ T cells emerged within 2 weeks of infection, persisted into the chronic phase, and accumulated in the infected ears but not the spleen, via a process that depended on local antigen presentation. T helper type‐1 (Th1) cells, not Foxp3+ regulatory T cells, were the chief producers of IL‐10 and were not exhausted. Therefore, tracking antigen‐specific CD4+ T cells revealed that IL‐10 production by Th1 cells is not due to persistent T‐cell antigen receptor stimulation, but rather driven by early antigen encounter at the site of infection.